Retailing in Electronic Commerce: Travel and Tourism Services Online - Mustakim, Mustakim (Universitas Muhammadiyah Enrekang, 2019)
In recent years, the emergence of new tourism services and products, coupled with a rapid increase in tourism demand, have driven the wide-scale adoption of ITs in general, and in particular, the Internet as an electronic intermediary. In other words, the Internet serves as a new communication and distribution channel for e-travelers and suppliers of travel services and products. This new channel also enables tourism businesses to improve their competitiveness and performance. The aim of this paper is to highlight how retailing in e-commerce (travel tourism service online) according to the experts is, special services, such as wireless services, direct marketing, alliances and consortia, benefits and limitation of travel online service, the impact of EC on the travel industry, corporate travel and intelligent agents in travel services.